All the president's women : Donald Trump and the making of a predator - Levine, Barry (Journalist); El-Faizy, Monique (Hachette Books, 2019)
During his 2016 presidential run, the revelation of the Access Hollywood tape and subsequent allegations of sexual misconduct lodged against Donald Trump looked like they might doom his candidacy. Trump survived, and the first two years of the real estate scion's presidency were marked not by controversy over his behavior around women but by the Mueller investigation. So far, Trump has dodged the #MeToo bullet that has taken down so many once-powerful men. But despite the decades of tabloid fascination with his personal life, the story of Trump's relationship with women has never been fully told. Considering his bully pulpit in the White House, the reckoning is overdue. All the President's Women offers the most detailed account yet of Trump's history with women, dating back to his childhood and high school days through his rise in real estate, reality TV, and politics. This book will show that Trump's behavior goes far beyond occasional "locker-room talk" and unwanted advances. Barry Levine and Monique El-Faizy detail more than a dozen new allegations against Trump, including a disturbing attack on a woman at Mar-a-Lago, an incident at a private Manhattan sex club involving a teenage girl, as well as Trump's behavior at fashion shows and beauty pageants--events that gave the future president a hunting ground to harass young women. Veteran journalists Levine and El-Faizy tell the story of Trump from the point of view of the women in his orbit--wives, mistresses, playmates, and those whom the president has dated, kissed, groped, or lusted after.